Sistem Informasi Absensi Pegawai Menggunakan Location Based Service pada Kantor Camat Berbasis Website - Salsabillah, Ayna; Kurniawan R, Rakhmat (Journal of Information System Research (JOSH), 2024)
Employee attendance information system is one of the important components in human resource management, especially in recording employee attendance and absence. This research aims to design and implement an Employee Attendance Information System using Location Based Service (LBS) at the Sibolangit Sub-District Office. This system utilizes LBS technology to ensure the accuracy of employee location when taking attendance, so as to prevent fraud that may occur with conventional attendance systems. By utilizing GPS-equipped mobile devices, this system allows employees to take attendance only when they are within a predetermined area around the Sibolangit Sub-District Office. The system consists of several main modules, namely employee authentication module, location recording module, and attendance report module. The recorded attendance data will be automatically stored in the database and can be accessed by the staffing department for monitoring and reporting purposes. System testing results show that this LBS-based attendance system can run well and provide accurate results. In addition, this system also received a positive response from employees who felt that this system was easier and more transparent. The implementation of this system is expected to improve employee discipline and efficiency in managing attendance data at the Sibolangit Sub-District Office.